Pemberdayaan Masyarakat Non Produktif Kecamatan Baleendah Kabupaten Bandung melalui Budidaya Tanaman Hias - Hizqiyah, Ida Yayu Nurul; Suteja, Jaja; Toharudin, Uus; Ibrahim, Yusuf; Cartono, Cartono; Darta, Darta; Riani, Dini; Harmaen, Dheni (Jurnal Indonesia Mengabdi, 2022)
During the current pandemic, people are looking for activities that can fill their spare time, one of which is the cultivation of ornamental plants. In addition to channeling hobbies, ornamental plant cultivation can increase people's income by marketing products to the market. The purpose of this activity is to provide knowledge and skills in the cultivation of Sirih Gading (Epipremnum aureum) ornamental plants vegetatively and by cuttings, to partners and provide information about business prospects and marketing strategies for fruit and ornamental plants in Griya Prima Asri Complex, Kec. Baleendah, Kab. Bandung. The selection of the Sirih Gading (Epipremnum aureum) ornamental plant as the object of service because this plant can grow in Indonesian climatic conditions, easy to care for, easy to observe and measure its growth, such as number of leaves, leaf width, leaf length, stem height, and root length. In addition, marketing assistance for ornamental plant products and fruit plants that are developed vegetatively is also carried out. The methods used are socialization, workshops/training, and monitoring. The results of this activity were 90% of the participants stated that the ornamental plant propagation training provided benefits and knowledge to cultivate and develop them into entrepreneurial prospects, in the midst of many people who lost their jobs due to the impact of the pandemic.